Convertible active power filter: A new approach to compensate for current quality problems in the DS - Mohammed, B.S. (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper presents a new moveable power quality (PQ) conditioner named convertible active power filter (CAPF) which aims to compensate for current quality (CQ) problems in the industrial, commercial or residential areas. The proposed CAPF has the capability and flexibility to change its compensation mode from load-To-load based on the variations of the load characteristics. This is absolutely necessary in distribution systems because the behavior of the consumer appliances varies continuously. The proposed controller algorithm which is based on the adaptive neural network (ADLINE) and fuzzy logic controller (FLC) is responsible for monitoring the CQ of each load and invoking the CAPF to start the compensation job by connecting the voltage source converter (VSC) based CAPF automatically to the corresponding load based on the total harmonic distortion (THD) of each load, sensitivity of the load to the CQ problems or changes in the load conditions. Power system electromagnetic transient simulation program (PSCAD/EMTDC) is used to simulate the CAPF, the simulation results showed that the proposed CAPF is capable to change its compensation mode from load-To-load to improve the PQ of the selected load based on the existence of CQ problems in the system or change in the load conditions. Â© 2015 IEEE.